Collections - Nationalmuseum (2006)
[Dt.:] Die Website bietet eine Bilddatenbank über die die Sammlung des Schwedischen Nationalmuseums in Stockholm online durchsucht werden. - [Engl.:] The website provides an online database of the National Museum of Fine Arts' collection. Here you will find out more about objects and artists in Nationalmuseum’s collections. You may also choose to explore them from a particular theme